DEVELOPMENT OF INTERACTIVE MULTIMEDIA TEACHING MATERIALS: VOIP SERVER INSTALLATION AND CONFIGURATION - Fahmy Syahputra; Atan Fices Barus (Sean Institute, 2022)
VOIP stands for Voice Over Internet Protocol or commonly called digital phone is a part of the transmission technology for transmitting voice communications over IP, such as the internet or packet-switched networks. By using VoIP, we can make telephone calls through an internet connection, no longer using conventional telephone lines that transmit analogue. That material will be developed into Android-based learning media, so that learning media is easier and more interesting to access.